Comparison of the efficiency of three methods of bacteriological analysis in the investigation of bacterial contamination of drinking water in Nineveh governorate - Muhsin Alagaidy; Angham Alagaidy (College of Education for Pure Sciences, 1970)
ABSTRACT This research was performed to compare the efficiency of three methods for bacteriological analysis of drinking water, Most Probable Number (MPN), Membrane Filtration (MF) and Total Plate Count (TPC) in detection of microbial contamination of drinking water in Nineveh province for two months, result showed differences in the percentage contamination of drinking water samples taken from one part depending on the method type, and the higher average in failure percentage appeared by using (MF) method (%67.77) followed by (MPN) method (%58.88) and then (TPC) method (%50), also (MF) results changed (%43.2) of accepted results in (MPN) method into failure results, and country sides was the most higher in average of failure percentage (%73.3).